The little stranger [compact disc, unabridged] - Waters, Sarah, 1966- (Penguin Audio, 2009)
Sunday Times Young Writer of the Year Award winner and London novelist Sarah Waters presents The Little Stranger, an eerie and thrilling tale set in post-World War II rural Britain. When Dr. Faraday, a Warwickshire physician, pays a visit to the Ayres family at their Hundreds Hall estate, he unknowingly enters a wickedly haunted house. His life soon becomes entwined with a family plagued by a terrifying past.